A Cartesian grid generation technique for 2-D non-Newtonian blood flow through a bileaflet mechanical heart valve. Issue 4 (4th July 2021) - Belkhiri, Khellaf; Boumeddane, Boussad
Abstract: Non-Newtonian blood flow through an aortic bileaflet mechanical heart valve is investigated numerically using the Casson model for the shear thinning behavior of the blood. The objective of this study is to deal with the influence of the non-Newtonian property of blood as well as of geometry of the prosthesis on flow phenomena and wall shear stress during the peak systolic phase. A comparison of non-Newtonian and Newtonian results is also presented. A nonuniform Cartesian grid generation technique is presented to generate a two-dimensional grid for the irregular geometry of the Butterfly valve. The governing Navier–Stokes equations of the flow, written in a stream function-vorticity formulation, are solved by the finite difference method with hybrid differencing of the convective terms. The results obtained with the model show that the blood non-Newtonian behavior induces a flow deceleration with the existence recirculation and consequently stagnation causing thrombus formation, as well as an increase of the shear stress along the wall which contributes the hemolytic blood damage; this is in agreement with the clinical observations concerning thromboembolic problems.